Effect of tensile strain on the band structure and carrier transport of germanium monosulphide monolayer: a first‐principles study. (1st May 2018) - Guo, Guanxing; Bi, Gang
Abstract : The electronic properties of germanium monosulphide (GeS) monolayer under tensile strain were investigated using first‐principles calculations. Our computations showed that the band gap of GeS monolayer was tuned from 1.96 to 2.72 eV via uniaxial and biaxial tensile strain in the range of 10%. Besides, two transitions involving indirect to direct and direct to indirect were triggered when GeS monolayer was applied 3.5 and 9% tensile strain in the zigzag direction, however this transition had not happened when the tensile strain was applied in the armchair and biaxial direction. The band gap variations of GeS monolayer with the tensile strain were explained using a bond nature mechanism based on the Heitler–London's exchange energy model. Moreover, upon applying external strain, the acoustic phonon limited carrier mobility of GeS monolayer had an enhancement with more than two orders of magnitude at 300 K, from 2.40 × 10 3 to 8.11 × 10 5 c m 2 V − 1 s − 1 . These findings show that strain engineering is an effective way to tune the electronic properties of GeS monolayer and to extend the applications of GeS monolayer in the field of electronics and optoelectronics.